Desempenho da cultura da soja na microbacia do Alto do Paranapanema baseado em modelagem de culturas - Moreira, Robson Rodrigues (Universidade Federal de São Carlos, 2022)
The soybean crop (Glycine max L.) is the main agricultural economic crop in Brazil. In 2018/2019 harvest it reached almost 114million of tons. Due to the physicochemical characteristics of the grains, it is widely used in human food, especially animals. However environmental variables and crop management are factors that can limit crop yield. Thus, technologies can help to increase crop yield, such as irrigation, different sowing periods and crop models tools. The region of interest, the upper Paranapanema micro basin, lacks data on crop yield in the agricultural sector, using generic indications from the state of São Paulo. Therefore, this proposal aims to evaluate soybean crop yield according to the different sowing dates, irrigation management and different sites based on DSSAT Cropgro-soybean crop model using 12 weather databases from different sites in the micro basin. These will be used to found potential crop yield for each site from 2009 to 2019 harvests. It was analyzed, in order to consider 12 different sites, 8 sowing dates and 6 water depths with available water capacity (CAD) parameter in the soil. The results were submitted to ANOVA and Tukey, which were mapped and georeferenced on the region map. The average yield achievable was 2540 kg ha-1, with the municipality of Apiaí being the most efficient with 64.7%. The irrigation depth of 100% of the CAD was more efficient, as well as the sowing between the months of September and December, with an average of 2600 kg ha-1.
Performance of soybean crop in the Alto do Paranapanema microbasin based on crop modeling
Keywords: DSSAT; Lâmina de irrigação; Produtividade; Semeadura; CIENCIAS AGRARIAS::AGRONOMIA